The Biesheim cameo – a reinterpretation - Juhász, Lajos (Dissertationes Archaeologicae, 2013)
In this paper I will analyse in depth the Biesheim cameo to which only minor attention was paid until now. There are still some parts of the interpretation that do not fit well together. This is why I have tried to undertake a thorough iconographic analysis that resolved in a new interpretation. In my opinion, the defeated enemy on the cameo can only be Armenia, instead of a Quadic king. Then again the rider is not likely to be Commodus, as previously thought, but rather Lucius Verus. This theory is also supported by a number of personifications of Armenia that were frequent in this period.